2023
DOI: 10.3390/agronomy13092343
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Mechanism of Melatonin Enhancing the Tolerance of Oat Seedlings under Saline–Alkali Stress

Qiang Wang,
Xiaotian Liang,
Dabing Xiang
et al.

Abstract: Exogenous melatonin (MT) regulates plant growth and mitigates stress in response to stress. To analyze the machinery of exogenous melatonin, which improves salt and alkaline tolerance in oats, MT’s function was identified in the oat seed germination stage in our previous study. In this study, morphogenesis, photosynthetic physiology, hormone levels, and ion homeostasis were evaluated using the same MT treatment concentration. The results revealed that compared to the S45 treatment, the 100 μmol·L−1 MT treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(75 reference statements)
0
2
0
Order By: Relevance
“… 43 When plants are subjected to adversity stress, the plant body’s own antioxidant mechanism is disrupted, resulting in the accumulation of large amounts of reactive oxygen species (ROS), which leads to changes in the permeability of the cell membrane. 44 After the cell membrane is disrupted, excessive accumulation of ROS leads to an increase in MDA content. We found that: the MDA content of leaves were decreased continuously under saline and alkaline stress, while in roots were not synchronized with leaves changes.…”
Section: Discussionmentioning
confidence: 99%
“… 43 When plants are subjected to adversity stress, the plant body’s own antioxidant mechanism is disrupted, resulting in the accumulation of large amounts of reactive oxygen species (ROS), which leads to changes in the permeability of the cell membrane. 44 After the cell membrane is disrupted, excessive accumulation of ROS leads to an increase in MDA content. We found that: the MDA content of leaves were decreased continuously under saline and alkaline stress, while in roots were not synchronized with leaves changes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they offer the capacity to manage insect pest management activity against storage and crop pests through various mechanisms, including physical distortion, diminished fertility, decreased egg deposition, and repellent activity. [10][11][12] During seed storage, it is essential to protect seeds in storage from storage insect pests and enhance their viability. With this in mind, the aim of the present study was to perform a comparative analysis of the insecticidal value and agro-morphological characteristics of maize from seeds treated using nonbiogenic and biogenic ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%